Estratégias e táticas cotidianas : um estudo sobre os sentidos das práticas sociais e suas influências no fazer estratégia de uma barraca em feiras-livres - Peixoto, Daniel Lanna (2011)
The word strategy has gained ground in academic writings, speeches and consulting. Despite the increased use of the word there is still a gap between talking about strategy and what people really acomplish in practice relating to directions taken by the o